1997
DOI: 10.1086/516494
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Human Monocytes withMycobacterium tuberculosisEnhances Human Immunodeficiency Virus Type 1 Replication and Transmission to T Cells

Abstract: Mycobacterium tuberculosis and human immunodeficiency virus type 1 (HIV-1) are virulent intracellular pathogens that invade and multiply within macrophages. The effect of M. tuberculosis on HIV-1 infection and replication was analyzed in vitro using human monocyte-derived macrophages (MDM) isolated from peripheral blood mononuclear cells by countercurrent centrifugal elutriation. Preinfection of MDM with M. tuberculosis followed by HIV-1 infection resulted in an increase in p24 release, reverse transcriptase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 17 publications
0
46
4
Order By: Relevance
“…Similar to monocytic THP-1 cells, primary adherent blood monocytes increase HIV-1 replication after infection with M. tuberculosis (7,11). We previously observed that M. tuberculosis suppresses HIV-1 replication in THP-1 cells differentiated to a macrophage-like state by treatment with PMA (15).…”
Section: Tuberculosis Complex Infection Suppressed Hiv-1 Replicatimentioning
confidence: 82%
See 2 more Smart Citations
“…Similar to monocytic THP-1 cells, primary adherent blood monocytes increase HIV-1 replication after infection with M. tuberculosis (7,11). We previously observed that M. tuberculosis suppresses HIV-1 replication in THP-1 cells differentiated to a macrophage-like state by treatment with PMA (15).…”
Section: Tuberculosis Complex Infection Suppressed Hiv-1 Replicatimentioning
confidence: 82%
“…Mutation of the C/EBP sites in the LTR produces a virus that continues to replicate in lymphocytes, but is no longer able to replicate in macrophages (21). Monocytic THP-1 cells and primary monocytes are able to up-regulate HIV-1 replication after infection with M. tuberculosis or stimulation with LPS (11,22). The enhancing effects of proinflammatory stimuli require intact C/EBP and NF-B sites in the HIV-1 LTR (6, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, while reporting an enhancement of HIV p24/RT levels accompanied by cytokine secretion or cytokine-mediated NF-kB-dependent transcriptional activation, did not demonstrate fully a link between these events (Zhang et al, 1995;Goletti et al, 1996Goletti et al, , 1998Vanham et al, 1996). Mancino et al (1997) have reported that viable but not heat-killed M. tuberculosis mediated an increase in HIV production in monocyte-derived macrophages, while Dezzutti et al (1999) have shown that heat-killed and viable MAC enhanced the replication of lymphocytotropic HIV-1 strain LAI in CD8-depleted PBMCs to comparable levels. They have shown further that matrix metalloproteinases are involved in in vitro M. aviuminduced HIV-1 replication in CD8-depleted PBMCs, which are mainly independent of cytokine secretion (Dezzutti et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…During the normal immune response, macrophages serve as APCs to present foreign antigens to CD4-expressing T lymphocytes. Intimate contact between an APC and a T cell leads to the upregulation of costimulatory molecules (e.g., CD80/CD86 on macrophages and CTLA-4 and CD40L on T cells) as well as the activation of HIV-1 transcription and production (35,38,50,51). Thus, it can be proposed that antigen presentation and/or the presence of some specific cytokines in the milieu surrounding HIV-1-infected macrophages will result in the expression of CD80 and CD86 and also in the production of HIV-1 particles bearing CD80 and CD86 in their envelopes.…”
Section: Discussionmentioning
confidence: 99%